International Handbook of Trade Unions - Schnabel, Claus; Addison, John T. (Edward Elgar, 2003)
'This volume is the definitive word on the topic, and likely will remain so for some time. The editors have done a remarkable job of compiling a list of contributors that reads like a "Who's Who" on the topic, ensuring quality control and summarizing a daunting amount of material. Given the dramatic changes that have been occurring throughout the world with respect to trade unions, this is a timely and welcomed contribution.'- Morley Gunderson, University of Toronto, Canada.'A fine collection, written by the world's leading experts in this important area. If you want to know about what has been happening at the frontier of recent research on unions, this is the book for you.'- Andrew J. Oswald, University of Warwick, UK. This Handbook is an authoritative and invaluable reference tool, uniquely analysing the forces governing unionism, union behaviour and union impact from a variety of perspectives, both theoretical and empirical. The 14 chapters are written in an accessible style by acknowledged leading specialists from the fields of economics and industrial relations. They offer a truly international perspective on this important subject. © John T. Addison and Claus Schnabel 2003. All rights reserve
UnivIS-Import:2015-04-02:Pub.2003.rw.fbwiwi.intern
Keywords: trade unions